PORE WATER GEOCHEMISTRY OF EASTERN MEDITERRANEAN MUD VOLCANOES: IMPLICATIONS FOR FLUID TRANSPORT AND FLUID ORIGIN - Haese R.R.; De Lange G.J.; Hensen C. (My University, 2006)
The pore water chemistry of mud volcanoes from the Olimpi Mud Volcano Field and the Anaximander Mountains in the eastern Mediterranean Sea have been studied for three major purposes: (1) modes and velocities of fluid transport were derived to assess the role of (upward) advection, and bioirrigation for benthic fluxes. (2) Differences in the fluid chemistry at sites of Milano mud volcano (Olimpi area) were compiled in a map to illustrate the spatial heterogeneity reflecting differences in fluid origin and transport in discrete conduits in near proximity. (3) Formation water temperatures of seeping fluids were calculated from theoretical geothermometers to predict the depth of fluid origin and geochemical reactions in the deeper subsurface. No indications for downward advection as required for convection cells have been found. Instead, measured pore water profiles have been simulated successfully by accounting for upward advection and bioirrigation. Advective flow velocities are found to be generally moderate (3-50 cm y- 1) compared to other cold seep areas. Depth-integrated rates of bioirrigation are 1-2 orders of magnitude higher than advective flow velocities documenting the importance of bioirrigation for flux considerations in surface sediments. Calculated formation water temperatures from the Anaximander Mountains are in the range of 80 to 145°C suggesting a fluid origin from a depth zone associated with the seismic decollement. It is proposed that at that depth clay mineral dehydration leads to the formation and advection of fluids reduced in salinity relative to sea water. This explains the ubiquitous pore water freshening observed in surface sediments of the Anaximander Mountain area. Multiple fluid sources and formation water temperatures of 55 to 80°C were derived for expelled fluids of the Olimpi area. © 2005 Elsevier B.V. All rights reserved.
Keywords: ADVECTION; BIOIRRIGATION; COLD SEEP; MUD VOLCANO; SUBSURFACE